HOW ETHICAL ARE EMOTIONALLY INTELLIGENCE PEOPLE? - MEUTIA KARUNIA DEWI (Faculty of Economics and Business, Jenderal Soedirman University, 2019)
Emotional intelligence has become an interesting discussion in organizational behavior field since it was introduced in 1989. A lot of researches have proven that this type of ability is important in shaping someone’s attitudes and behaviors. Nevertheless, only few studies have inquired the effect of emotional intelligence on how good or bad people’s attitudes and behavior. Thus, this research tried to find out the connection between emotional intelligence and morality. The participants of this research are 149 Management and Accounting program students of Economics and Business Faculty in Jenderal Soedirman University. More explanation about our result and implications are followed at the end of this article.